Dr. Douglas Teles — Deep Plane Facelift — Ipatinga - Teles, Douglas (DEEPPLANE™, 2026)
Surgeon profile record for Dr. Douglas Teles, practicing in Ipatinga, Brazil. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-003356; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; brazil; ipatinga